Depression and intimate relationships of adolescents from divorced families - Halima Hadžikapetanović; Tajib Babić; Edin Bjelošević (Medicinski glasnik, 2017)
Aim: To determine an impact of parental divorce to depression and intimate relationships of young people during adolescence, and prevalence of symptoms of depression and the level of intimacy in relations to adolescents living in intact families and those from divorced families. Methods: This prospective descriptive research was conducted on a sample of 168 examinees of which 64 (38.1%) were students of the University Zenica, and 104 (61.9%) high students schools from Zenica and Maglaj cities during May and June 2011. Beck’s Depression Inventory (BDI) II, Miller Social Intimacy Scale and sociodemographic questionnaire were used. Results: Adolescents from divorced families had statistically significantly higher level of depression (p<0.05), with moderate and severe depression found in 20 (24.69%) adolescents from divorced families as compared with six (6.89%) adolescents from intact families. An analysis of BDI-II scale showed that adolescents from divorced families had statistically significant difference in agitation (p< 0.01), difficult concentration, suicidal thoughts, grief and pessimism (p<0.05). Conclusion: It is necessary to carry out detailed studies on longterm effects of breakup of families due to divorce, which have negative implications on psychological and social functioning of adolescents and the development of their identity and closeness in intimate relationships, with a legislative introduction of premarital and marriage counseling for parents in the conflict.
Keywords: depression; adolescents; marriage; divorce; intimacy; family